Racialized Others in Frankenstein and Wuthering Heights - Nieminen, Ellen (My University, 2016)
In my thesis I analyze two classic English novels, Emily Brontë’s Wuthering Heights and Mary Shelley’s Frankenstein from a postcolonial perspective. I focus on the two central characters in the novels, Heathcliff and Frankenstein’s monster, who are both outsiders and markedly racialized agents in the narratives. Using Edward Said’s theory on Orientalism and Anne McClintock’s theory on imperialism and domesticity, I argue that the Monster and Heathcliff represent European anxieties concerning various issues linked with imperial expansion and identity politics. The Monster and Heathcliff are both disruptive forces in the narratives and they ultimately reveal the problematic nature of colonial attitudes which also reflect domestic power structures of gender and class. Ultimately the Monster and Heathcliff are ambiguous characters who refuse to occupy any specific role in the narrative and remain as undefined and ambivalent figures in the story.